Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.infbeh.2007.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Newborn right-holding is related to depressive symptoms in bottle-feeding mothers but not in breastfeeding mothers

Abstract: This study examines the relationships between infant holding preferences and maternal depression according to the newborn feeding mode. Links between depression and infant holding biases have been observed in mothers [Vauclair, J., Scola, C. (in press). Dépression, alexithymie et latéralisation dans la façon de porter un nouveau-né [Infant holding biases in relation to depression, alexithymia and laterality]. Annales Médico-psychologiques; Weatherill, R. P., Almerigi, J. B., Levendosky, A. A., Bogat, G. A., vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…A pericardial effusion is the most frequent cardiac manifestation. Hypothyroidism is associated with an increased risk for atherosclerosis and ischemic heart disease and is now considered as proatherosclerosis factor[6,7]. Many of the cardiac manifestations of thyroid dysfunction are associated with alterations in T3-mediated gene expression 8.…”
Section: Discussionmentioning
confidence: 99%
“…A pericardial effusion is the most frequent cardiac manifestation. Hypothyroidism is associated with an increased risk for atherosclerosis and ischemic heart disease and is now considered as proatherosclerosis factor[6,7]. Many of the cardiac manifestations of thyroid dysfunction are associated with alterations in T3-mediated gene expression 8.…”
Section: Discussionmentioning
confidence: 99%
“…The question is whether this might influence the mother's psychological well-being. The fact that there is a clear association between depression and right-arm cradling (e.g., Weatherill et al, 2004), and that one study investigating cradling preference found this association in bottle-feeding but not in breast-feeding mothers who often hold their infant on the left arm as well (Donnot, Vauclair, & Brejard, 2008), does indeed suggest such a connection, although the causal relation may just as well be the other way around (i.e., negative affect causing right-holding preference). If decrements in infant's face visibility from the mother's point of view do indeed aggravate or even cause negative maternal affect, the consequences could be serious for the child as well (for a recent review, see Wachs, Black, & Engle, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of cradling bias during bottle feeding in clinically depressed mothers demonstrated a tendency of the mother to cradle her baby to the right. The authors concluded that cradling behaviour in this circumstance was not due to a hemispheric Specialization, but rather those higher levels of depression were associated in some other way with influencing cradling while bottlefeeding [38].…”
Section: Cradling and Breast-feedingmentioning
confidence: 96%
“…The theory being explored proposed that breast feeding positioning preferences were the causal factor in leftward cradling. An investigation by Donnot et al [38] explored the behaviours of cradling by depressed mothers during feeding using both bottle-feeding and breast-feeding as variables. The subjects in the study were divided into two groups consisting of mothers who had been diagnosed as depressed, and those who had not.…”
Section: Cradling and Breast-feedingmentioning
confidence: 99%